Physiological modulation of endogenous BRCA1 p220 abundance suppresses DNA damage during the cell cycle - Dimitrov, Stoil D. (Cold Spring Harbor Laboratory Press, 2013)
Endogenous BRCA1 p220 expression peaks in S and G2 when it is activated, and the protein participates in certain key DNA damage responses. In contrast, its expression is markedly reduced in G0/G1. While variations in transcription represent a significant part of p220 expression control, there is at least one other relevant process. We found that a microRNA, miR-545, that is expressed throughout the cell cycle down-modulates endogenous p220 mRNA and protein abundance directly in both G0/G1 and S/G2. When miR-545 function was inhibited by a specific antagomir, endogenous p220 expression increased in G0/G1, and aberrant p220-associated DNA damage responses and de novo DNA strand breaks accumulated. Analogous results were observed upon inhibition of miR-545 function in S/G2. Both sets of antagomir effects were mimicked by infecting cells with a p220 cDNA-encoding adenoviral vector. Thus, strand breaks were a product of p220 overexpression, and their prevention by miR-545 depends on its modulation of p220 expression. Breaks were also dependent on aberrant, overexpressed p220-driven recruitment of RAD51 to either spontaneously arising or mutagen-based DNA damage sites. Hence, when its level is not physiologically maintained, endogenous p220 aberrantly directs at least one DNA repair protein, RAD51, to damage sites, where their action contributes to the development of de novo DNA damage. Thus, like its loss, a surfeit of endogenous p220 function represents a threat to genome integrity.